Effect of Digital Banking and Digital Transformation on the Efficiency of Nepalese Commercial Banks - Joshi, Prajwol Raj (Nepalese Journal of Finance, 2025)
This study examines the effect of digital banking and digital transformation on the efficiency of Nepalese commercial banks. Efficiency is the dependent variable. The selected independent variables are ATM banking, internet banking, mobile banking, SMS banking, NEFT/RTGS and e-payment systems. The primary sources of data is used to assess the opinions of respondents regarding ATM banking, internet banking, mobile banking, SMS banking, NEFT/RTGS, e-payment systems and efficiency of banks. The study is based on the primary data of 127 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of effect of digital banking and digital transformation on the efficiency of Nepalese commercial banks. The study showed a positive impact of ATM banking on efficiency. It indicates that ATM banking provided by banks leads to increase in efficiency of banks. Similarly, the study showed a positive impact of internet banking on efficiency. It indicates that adoption of internet banking leads to increase in efficiency of banks. Likewise, the study showed a positive impact of mobile banking on efficiency. It indicates that secure online transactions through mobile banking leads to increase in efficiency of banks. Further, the study also showed a positive impact of SMS banking on efficiency. It indicates that faster and more organized banking leads to increase in efficiency of banks. In addition, the study showed a positive impact of NEFT/RTGS on efficiency. It indicates that faster online transactions through NEFT/RTGS systems leads to increase in efficiency of banks. Moreover, the study showed a positive impact of e-payment system on efficiency. It indicates that user friendly online payment system leads to increase in efficiency of banks.